"Why me?": Qualitative research on why patients ask, what they mean, how they answer and what factors and processes are involved - Robert Klitzman (Elsevier, 2023)
Patients often ask, "why me?" but questions arise regarding what this statement means, how, when and why patients ask, how they answer and why. Interviews were conducted as part of several qualitative research studies exploring how patients view and cope with various conditions, including HIV, cancer, Huntington's disease and infertility. A secondary qualitative analysis was performed. Many patients ask, "why me?" but this statement emerges as having varying meanings, and entailing complex psychosocial processes. Patients commonly recognize that this question may lack a clear answer and that asking it is irrational, but they ask nonetheless, given the roles of unknown factors and chance in disease causation, psychological stresses of illness and lack of definitive answers. Patients may focus on different aspects of the question - e.g., on possible causes of illness (Why me? - whether God or randomness is involved) and/or on whether they are being singled out and/or punished (Why me vs. someone else?). Patients frequently undergo dynamic processes, confronting this question at various points, and arriving at different answers, looking for explanations that have narrative coherence for them, and make sense to them emotionally. Social contexts can affect these processes, with friends, family, providers or others rejecting or accepting patients' responses to this question (e.g., beliefs about whether the patient is being punished and/or these questions are worth asking). Anger, depression, despair and/or resistance to notions about the roles of randomness or chaos can also shape these processes. While prior studies have each operationalized "why me?" in differing ways, focusing on varying aspects of it, the concept emerges here as highly multidimensional, involving complex processes and often affected by social contexts. These data, the first to examine key aspects and meanings of the phrase, "why me?" have critical implications for future practice, research and education.